The effect of heat input on microstructure and HAZ expansion in dissimilar joints between API5L X80 / DSS 2205 steels using thermal cycles - Seyed Meisam Zahraei; Reza Dehmolaei; Ali Ashrafi (Revista de Metalurgia, 2022)
In this research, the effect of the shielded metal arc welding (SMAW) process heat input upon the microstructure and development of the heat-affected zone in the dissimilar joint of API 5L X80/DS5 2205 steels was investigated by recording the thermal cycles with thermocouple implantation in the perpendicular direction of the weld line. The filler metal used (electrode) is DSS 2209. The microstructure of the base and weld metals and their interfaces at different heat inputs were investigated using the scanning electron microscopy/energy-dispersive spectroscopy analysis technique (SEM/EDS) and optical microscopy (OM). The results indicated that the interface between the base metals and the weld metal has excellent consistency and that there is no evidence of cracks at different heat inputs. By increasing the heat input, it was determined that the amount of secondary austenite in the weld metal and heat-affected zone of 2205 steel had been increased. There occurred an epitaxial growth at the interface of 2209/2205, and there were a fine transition zone and Type II boundaries at the interface of 2209/ API 5L X80. The areas containing coarse, fine, and partially fine grains were detected in the heat-affected zone of the X80 steel. The thermal cycle results determined that the temperature peak in the areas away from the fusion line had increased by increasing the heat input and that the heat-affected zone of the two base metals, particularly the X80 steel, had been extended further.